Magic box remindeR (MBR) system using IOT technology - Md.Ali, Rozita Binti; Mohd Zain, Suhaila Binti; Shafie, Mohd Suhaidi Bin (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
Medication non-adherence is major problem for high dependent treatment such as diabetic patients. Several barriers and factors impacting medication non-adherence are, age, ethnicity, literacy, social status, patient–clinician relationship, patient’s misunderstanding or lack of knowledge, poor perception of illness and treatment efficacy. Therefore, patients need tools to reminds them to take medicine on time. The role of taking medication is important in the daily life of chronic patients. In addition, the delay in taking medicine will cause adverse health effects, for example, patient's blood sugar level to rise and unstable. Recently, medication neglect in chronic patients, has lead in deaths increase. Therefore, a magic box reminder is developed using Agile methodology to address this problem. It is sophisticated technology using Internet of Thing (IOT) technology that can help patients who forget to take medication. It helps to remind the patients to take medicine using a buzzer from the box and tell the patients about the medicine through the smartphone application. The notifications will display in Android platform. The patients can fully utilize the magic box from its convenient setting and easy functions. Thus, perhaps increase their health and longer life.